Administration of justice in Umar Farooq's Caliphate - Farooqui, Jamil (Radiance Views Weekly, 2014)
Governance is defined as administering and managing the affairs of a state in such a way as to provide the people with better life conditions, directing them to the appropriate path and achieving the purpose for which the state is formed. It generally refers to the government, the principles on and for which it works and the strategy it adopts to create conducive conditions for leading a peaceful and dignified life.